Cosmology 2020 The Current State - Smith, Michael L. (IntechOpen, 2020)
Cosmology 2020 - The Current State offers the reader several fresh ideas on this topic. The first chapter presents an argument that, both in theory and in reality, one cannot ignore the microscopic world to concentrate on the Universe at only the galactic level. Then we have several chapters presenting new explanations for dark energy and dark matter based on reasonable physics at the atomic level. We cover the beginnings of artificial intelligence to model a cosmological phenomenon and a chapter pointing out that better results can be culled from SNe Ia and HII data when appropriate computerised analyses are applied. We think this book will add some new ideas to the libraries of many cosmologists and astrophysicists.